Microstructural, mechanical and thermodynamic properties ınvestigation of the novel rare earth-free multicomponent Mg-15Al-8Ca-3Zn-2Ba alloy - Türe, Yiğit (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
There has been a significant increase in research and development efforts to meet the growing demand for environmentally friendly magnesium (Mg) alloys. Studies are currently exploring different combinations of alloying elements to meet the demanding specifications. The aim of this studywas to examine the usability of the elements aluminum (Al), calcium (Ca), and zinc (Zn) together with barium (Ba), and to investigate the mechanical and thermodynamic properties of the resulting multicomponent alloy system. SEM and hardness tests were used to examine the microstructural and mechanical properties of the Mg alloys. In the SEM analysis, the alloy was determined to consist of an α-Mg matrix, a block-like compact structure containing Ba (Mg17Ba2), a regional eutectic structure (Ca2Mg6Zn3), and independently growing lamellae (Al2Ca). The general hardness analysis results of the alloy, measured by Brinell and Vickers tests, were determined to be ~77 and ~82, respectively. The indentation test also revealed that the stress transfer to the Al2Ca laves phase is possible, depending on the orientation of the slip plane between the matrix and the Al2Ca phase. It was also observed that cracks that developed on the intermetallic Mg17Ba2 phase in the indentation test were only formed in the high-stress regions of the structure, and their propagation was limited. According to the thermodynamic analysis, the ΔHmix value is -2.73 kJ/mol, the ΔSmix value is 5.95 J/molK, the δ value is 34%, the Δꭕ value is 0.14, and the Ω value is 2.03. The obtained thermodynamic data were found to be compatible with the microstructural development of the alloy.